2020
DOI: 10.1002/ijc.32892
|View full text |Cite
|
Sign up to set email alerts
|

Adult weight change and premenopausal breast cancer risk: A prospective pooled analysis of data from 628,463 women

Abstract: Early‐adulthood body size is strongly inversely associated with risk of premenopausal breast cancer. It is unclear whether subsequent changes in weight affect risk. We pooled individual‐level data from 17 prospective studies to investigate the association of weight change with premenopausal breast cancer risk, considering strata of initial weight, timing of weight change, other breast cancer risk factors and breast cancer subtype. Hazard ratios (HR) and 95% confidence intervals (CI) were obtained using Cox reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…When estimating the associations stratified by menopausal status, menopausal status was considered as a time-varying factor, so that the same woman could contribute person-time, for example, to both the premenopause and the postmenopause strata. Given that there is considerable heterogeneity in risk factor associations by tumor estrogen receptor (ER) status (31,32), analyses evaluating risk by ER status were also conducted. Smoking is one of the major modifiable risk factors for periodontal disease, and may be weakly associated with risk for breast cancer (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…When estimating the associations stratified by menopausal status, menopausal status was considered as a time-varying factor, so that the same woman could contribute person-time, for example, to both the premenopause and the postmenopause strata. Given that there is considerable heterogeneity in risk factor associations by tumor estrogen receptor (ER) status (31,32), analyses evaluating risk by ER status were also conducted. Smoking is one of the major modifiable risk factors for periodontal disease, and may be weakly associated with risk for breast cancer (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, from a life-course perspective, higher body fatness in childhood and adolescence is inversely related to the risk of pre-menopausal breast cancer as well as post-menopausal breast cancer 39 , suggesting a long-term protective effect of EBF on breast cancer risk later in life. Analysis from the cohortpooling project papers 40 on premenopausal breast cancer confirms that relative overweight at age 18-24 is associated with a modest reduction in the risk of pre-menopausal breast cancer up to the age of ~50 years, and additional analyses 41 Perspective-Cancer prevention through weight control -where are we in 2020? 11Evidence related to MR studies also indicates that a genetically predicted larger body size at age 10 might protect against breast cancer in women independent of subsequent body size at a mean age of 56.5 years 42 .…”
Section: Excess Body Fatness and Breast Cancer Riskmentioning
confidence: 96%
“…The allelic frequency of MTHFR 677T was 0.44 in the controls and 0.47 in the BC cases. Considering that BC is a complicated disease, many risk factors, such as body weight and menopause, are associated with the occurrence and progression of BC [ 17 ]. Therefore, we conducted a stratified analysis on data according to age, diabetes mellitus, presence of hypertension, family history of cancer, menopause, body mass index (BMI), tumor site, tumor size, and lymph node metastasis (LNM) stage to determine whether the MTHFR C677T polymorphism is associated with BC incidence in specific subtypes of the study population, as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%